Effects of effort praise on struggling Filipino ESL readers’ motivation and mindset - Calingasan, King Arman Alonzo; Plata, Sterling Miranda (Indonesian Journal of Applied Linguistics, 2022)
Previous research on praising students to improve their motivation and their mindset had mixed results. This inconsistency was the impetus for this paper. The present study employed a mixed-method experimental design to examine the effects of effort praise on reading motivation and mindset of 60 Filipino seventh-grade students who were categorized as frustration-level readers. They studied English as a second language (ESL) where they were expected to comprehend various texts with appropriate reading styles based on the Grade 7 curriculum guide of the Department of Education in the Philippines. Using the Implicit Theory Scale (Dweck et al., 1995), the study found that effort praise led students in the positive rule group to endorse a growth mindset, while the students in the inverse rule group adopted a fixed mindset after receiving effort praise. Moreover, although it may increase reading motivation, the positive effect of effort praise on struggling ESL readers with fixed and growth mindsets may be short-term. This paper concludes with a schematic diagram to illustrate and explain how effort praise affects the mindset and the motivation of struggling ESL adolescents in reading. It also provides practical recommendations to improve reading teachers’ practice of giving positive feedback, specifically effort praise.